(untitled) (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND: Colorectal cancer is the third and second leading cancer in men and women. It is the fourth and third death causing cancer in men and women, first occurring in the large intestine. Superoxide dismutase is a key antioxidant enzyme scavenging the superoxide radial. The superoxide dismutase is induced and helps to prevent colorectal cancer because it is a natural antioxidant present inside the body. The physical exercise helps to prevent colorectal cancer and also it increases the production of superoxide dismutase in the body. The lifestyle, obesity leads to cancer which can be prevented by physical exercise and it also induces the superoxide dismutase.AIM: To analyse the endogenous superoxide dismutase as a potential inhibitor for PI3K/AKT signaling to colorectal cancer.MATERIALS AND METHODS: It is a bioinformatic study that was conducted in a private dental college. The endogenous superoxide dismutase which is produced by exercises is used as the target protein. Retrieval of AKT, mTOR,PI3K protein from protein bank and Patchdock methods is used to find interaction between proteins. The interaction is visualised by using pymol colours intensity. The pdbsum was used to identify types of interaction occurring between the docking complex.RESULT: The result showed SOD and Akt, mToR, PI3K complexes were best in terms of global energy and atomic contact energy and also had a good number of hydrogen bonds interaction and hydrophobic contactsThe superoxide dismutase which can be produced by exercise has a positive interaction with AKT, PI3K and mTOR and it acts as a potential inhibitor for PI3K/AKT signaling and it acts as a protective factor in the colorectal cancer. CONCLUSION: From the study it is concluded that the role of exercise in producing the endogenous superoxide dismutase is suggested to act as a potential inhibitor for PI3K/AKT signaling in colorectal cancer. The exercise may help to maintain health by modulating PI3K/AKT signaling and acts as a protective factor in preventing and controlling colorectal cancer.